Investigation of activation-induced markers (AIM) in porcine T cells by flow cytometry - Moorton, Madison; Tng, Priscilla Y. L.; Inoue, Ryo; Netherton, Christopher L.; Gerner, Wilhelm; Schmidt, Selma (Frontiers in Veterinary Science, 2024)
Activation induced markers (AIMs) are frequently analysed to identify re-activated human memory T cells. However, in pigs the analysis of AIMs are still not very common. Based on available antibodies, we designed a multi-colour flow cytometry panel comprising pig-specific or cross-reactive antibodies against CD25, CD69, CD40L (CD154) and ICOS (CD278) combined with lineage/ surface markers against CD3, CD4 and CD8α. In addition, we included an antibody against tumor necrosis factor alpha (TNF-α), to study the correlation of AIM expression with the production of this abundant T cell cytokine. The panel was tested on peripheral blood mononuclear cells (PBMCs) stimulated with phorbol 12-myristate 13-acetate (PMA)/ionomycin, Staphylococcus enterotoxin B (SEB) or PBMCs from African swine fever virus (ASFV) convalescent pigs, restimulated with homologous virus. PMA/ionomycin resulted in a massive increase of CD25/CD69 co-expressing T cells of which only a subset produced TNF-α, whereas CD40L expression was largely associated with TNF-α production. SEB stimulation triggered substantially less AIM expression than PMA/ionomycin but also here CD25/CD69 expressing T cells were identified which did not produce TNF-α. In addition, CD40L-single positive and CD25+CD69+CD40L+TNF-α- T cells were identified. In ASFV restimulated T cells TNF-α production was associated with a substantial proportion of AIM expressing T cells but also here ASFV-reactive CD25+CD69+TNF-α- T cells were identified. Within CD8α+ CD4 T cells, several CD25/CD40L/CD69/ICOS defined phenotypes expanded significantly after ASFV restimulation. Hence, the combination of AIMs tested will allow the identification of primed T cells beyond the commonly used cytokine panels, improving capabilities to identify the full breadth of antigen-specific T cells in pigs.